Analysis of Readiness For the Preparation of MSME Financial Statements Based on Financial Accounting Standards (SAK)–EMKM (Case Study of Hj. Vera Furniture Store in Karawang Regency) - Wulansari, Wulansari; Carolyn Lukita; Devi Astriani (Jurnal Ekonomi, 2024)
MSMEs are one of the important roles in the Indonesian economy. This study aims to find out how the knowledge and readiness of the place that the author examined, namely the Hj. Vera furniture store, in preparing financial statements based on EMKM financial accounting standards (SAK). The research method is by using qualitative methods, which are case studies. Data collection is carried out by observation, interviews and documentation. This research was conducted to identify obstacles that occur in Hj. Vera furniture MSMEs and to prepare financial statements in accordance with applicable financial accounting standards. The results of this study show that MSMEs have problems in preparing financial statements, namely limited thinking about managing financial statements and limited inadequate human resources (HR) in preparing financial statements. Financial statements based on SAK EMKM, namely the statement of financial position, income statement, and notes to financial statements. This research is expected to contribute to MSME actors in Karawang district in order to understand how to prepare financial statements based on SAK EMKM.